Inovasi Penyuluhan Anti Bullying di Sekolah dan Implikasi Pengawasan Orang Tua terhadap Pemakaian Gadget - Armiya Nur Lailatul Izzah (https://journal.metanusantara.com/impact/index.php/jpk, 2025)
Bullying in the school environment remains a serious problem that impacts students' psychological and academic development. The development of technology has also expanded bullying into the digital realm (cyberbullying), which is increasingly difficult to control without innovation in counselling and supervision. This study aims to develop an innovative anti-bullying counselling model in schools and formulate effective strategies for parents in supervising children's use of gadgets to create a safe and conducive learning environment. This research uses the Participatory Action Research (PAR) method by involving students, teachers, and parents in several schools in Indonesia. Data were collected through observation, in-depth interviews, focus group discussions (FGDs), and surveys of students and parents. Data were analysed using a descriptive qualitative approach using thematic analysis techniques. The results showed that innovative anti-bullying counselling, such as the use of interactive educational media and integration in the curriculum, was effective in increasing students' understanding and reducing the incidence of bullying in schools. In addition, parental supervision of gadget use plays an important role in minimising children's involvement in cyberbullying. Children who receive closer supervision tend to have a higher awareness of using technology wisely. Thus, collaboration between schools and parents is a key factor in building a safe and inclusive education ecosystem for students.